Assessing the Readability of Clostridium difficile on the Internet: A Cross-Sectional Study. Issue 3 (3rd July 2019) - Basch, Corey Hannah; Fera, Joseph; Garcia, Philip
Abstract: Clostridium difficile ( C. diff ) is a bacterium that causes diarrhea and kills an estimated 29, 000 people per year (over one-half of which is directly attributable to C. diff). The objective of this study was to evaluate the readability of information on 100 English language websites related to C. diff . The first 100 English language websites resulting from a Google search were the sample. The analysis strongly indicated that websites providing information on C. diff are written at a reading level exceeding the recommended level. The majority of websites included in this sample were not written at the readability level recommended. Hence, it is recommended that information on the internet about C. diff be written at a level that is more accessible to a wide audience.